TEM characterization of stress corrosion cracks in 304SS - Lozano-Perez, S; Titchmarsh, J; Jenkins, M (2004)
This paper reports the analysis of a sample of type 304 stainless steel tested under constant load (CLT) in a simulated pressurized water reactor environment in which had developed a mixture of both long (of the order of mm) and short (a few microns) cracks. A duplex oxide layer structure was observed along the flanks of all cracks. The chemical composition of the two layers remained constant and independent of crack depth. However, differences were observed as a function of crack depth between the thicknesses and sizes of the spinel crystallites that composed the two layers. The implication of these observations for SCC mechanisms is described.